Thyroid Gland Rupture Associated with Blunt Cervical Trauma - a Case Report - Andrade Junior, Arymar Antonio (2017)
Although soft tissues injury in cervical trauma is relatively common, the injury of the thyroid is extremely rare, as we can see in English-language reports. The papers relate that trauma of the thyroid gland is quite rare in patients without preexisting goiter. This paper relates a blunt cervical trauma in a young woman without goiter disease that results in lesion of the thyroid diagnosed by computed tomography scan (CT) and that has been conduced conservatively, with a favorable course without further complications.